Protection and Security in a Technologically Advanced Society: Children and Young People’s Perspectives - Hannigan, Kerry (2014)
The continuous advancement of new technology, specifically in the area of internet technology, has led to an increase in concerns surrounding children and young people’s safety when online. The following thesis describes a study of protection and security on the internet from the perspective of children and young people and contributes and expands on the findings of my Masters Dissertation which examined parents’ perceptions of children at risk on the internet. The research focuses on young people’s perspectives about what risks they face and what would keep them safe and is set within literature on child sex abusers and internet grooming. The thesis is based on an online survey which gathered information about the behaviour and opinions of 859 children and young people living in Scotland. Findings were separated into four main topics: children and young people’s behaviour on the internet, children and young people’s perception of strangers both online and offline, children and young people’s opinion of education on internet safety and children and young people’s opinion of the government’s role in relation to their safety online. Respondents’ stated that they wanted to be protected when on the internet (whilst acknowledging their own responsibility when online), either by the government or through those responsible for the content of the internet. They also provided several suggestions on how schools and the government can do more to listen to their voices and improve internet safety education. There were a number of children and young people who reported that they disclosed personal information over the internet (their own and that of their friends and family) and that they were willing to meet people in the real environment whom they had been communicating with online: many respondents’ viewed internet ‘strangers’ as different from ‘strangers’ in the real environment. Vygotsky’s (1978) theory of the Zone of Proximal Development (ZPD) and Wood et al.’s (1976) development of the concept of scaffolding, which has been developed in an educational rather than criminological context, were identified as offering some promise for explaining the behaviour of both the victims and the offender as other theories of sexual offending (either specific theories or explanations developed from general theories) are incapable of fully providing an explanation that will encompass grooming in general and online grooming in particular. It is argued that if these theories are applied to internet safety education they have the potential to empower children and young people and make grooming tactics and approaches less effective. The findings also indicated that more child and young people-oriented protection measures may be needed. Perceptions of protection and security on the internet were wide ranging but respondents were keen to provide possible solutions and examples of how to improve their safety when online. This would suggest that communicating with children and young people when developing policy, legislation, research and educational materials is the way forward if we wish to improve their safety and eliminate or reduce the dangers they face when using the internet